DETERMINING USER SATISFACTION REGIONAL GOVERNMENT INFORMATION SYSTEM (SIPD) USING EUCS MODEL IN REGIONAL FINANCIAL MANAGEMENT - Mukhtar, Abdul Hakim; Muhammad Din; Rahayu Indriasari; Erwinsyah (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
This study aims to examine the factors influencing user satisfaction with the Regional Government Information System (SIPD) in Central Sulawesi Province using the End-User Computing Satisfaction (EUCS) model. This quantitative study employed a causal explanatory design with purposive sampling, involving 80 respondents consisting of Heads of Finance Subdivision and SIPD Operators from 40 Regional Device Organizations (OPD). Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with WarpPLS software. The results indicate that accuracy, ease of use, timeliness, and IT infrastructure have a significant positive effect on user satisfaction, while content, format, and privacy and security have positive but non-significant effects. These findings emphasize the importance of accurate information, user-friendly systems, timely data presentation, and robust technological infrastructure in enhancing SIPD user satisfaction. This study contributes to the development of information system quality theory and offers practical implications for local governments to improve financial governance through infrastructure strengthening and continuous content enhancement.